Genetic evidence for an inhibitory role of tomosyn in insulin‐stimulated GLUT4 exocytosis. (24th September 2020) - Wang, Shifeng; Liu, Yinghui; Crisman, Lauren; Wan, Chun; Miller, Jessica; Yu, Haijia; Shen, Jingshi
Abstract: Exocytosis is a vesicle fusion process driven by soluble N‐ethylmaleimide‐sensitive factor attachment protein receptors (SNAREs). A classic exocytic pathway is insulin‐stimulated translocation of the glucose transporter type 4 (GLUT4) from intracellular vesicles to the plasma membrane in adipocytes and skeletal muscles. The GLUT4 exocytic pathway plays a central role in maintaining blood glucose homeostasis and is compromised in insulin resistance and type 2 diabetes. A candidate regulator of GLUT4 exocytosis is tomosyn, a soluble protein expressed in adipocytes. Tomosyn directly binds to GLUT4 exocytic SNAREs in vitro but its role in GLUT4 exocytosis was unknown. In this work, we used CRISPR‐Cas9 genome editing to delete the two tomosyn‐encoding genes in adipocytes. We observed that both basal and insulin‐stimulated GLUT4 exocytosis was markedly elevated in the double knockout (DKO) cells. By contrast, adipocyte differentiation and insulin signaling remained intact in the DKO adipocytes. In a reconstituted liposome fusion assay, tomosyn inhibited all the SNARE complexes underlying GLUT4 exocytosis. The inhibitory activity of tomosyn was relieved by NSF and α‐SNAP, which act in concert to remove tomosyn from GLUT4 exocytic SNAREs. Together, these studies revealed an inhibitory role for tomosyn in insulin‐stimulated GLUT4 exocytosis in adipocytes. We suggest that tomosyn‐arrested SNAREs represent a reservoir of fusion capacity that could be harnessed to treat patients with insulin resistance and type 2 diabetes. Abstract : Insulin‐stimulated GLUT4 exocytosis plays a key role in the maintenance of blood glucose homeostasis, but its molecular basis remains incompletely understood. In this work, we demonstrate that the SNARE‐binding factor tomosyn negatively regulates GLUT4 exocytosis in adipocytes. At the molecular level, tomosyn arrests the assembly of GLUT4 exocytic SNAREs at an intermediate stage. The inhibitory activity of tomosyn is relieved by NSF and α‐SNAP, which act in concert to remove tomosyn from GLUT4 exocytic SNAREs.